Kelangsungan dan Perlawanan Tata Pemerintahan yang Baik di Tingkat Desa - OKTIARINI, CHRISTIANTI; DAMIS, MAHYUDDIN (Universitas Muhammadiyah Yogyakarta, 2010)
This paper is based on the study of political decentralization and the resistance is carried out in three areas,West Sumatra, Javanese and Batak. Obtained from the three research areas each of these karkteristikperalawanan and sustainability of the local nature of the resistance. There was found to give each region areligious response in the context of regional autonomy that has been ongoing since 1999 in Indonesia.Society against its own way that occasionally showed intensity that it seems it never ceases to deal with theconditions faced daily. While the country is also facing the community in its own way so it does not collidewith each other mutual support.